Leadership Conflicts in the Management of Madrasah Aliyah Educational Institutions in Indonesia - Muhammad Muhsin Saqafi Ezhari; Khairiah Khairiah (UIN Fatmawati Sukarno Bengkulu, 2023)
Abstract: In the management of educational institutions still creates conflicts, because some leadership is still weak at the level of management, competence and leadership ability in managing educational institutions. The purpose of this paper is not only to map but also to analyze leadership conflicts in the management of Madrasah Aliyah educational institutions in Indonesia. Using descriptive qualitative methods. Data sources from scientific books, scientific articles, scientific journals both print and online, both nationally and internationally. The results showed that leadership conflicts in education management occur because the level of management of educational institutions by some leadership is still weak such as weak in planning, organization, movement, direction and supervision or control. Leadership conflicts also occur because the level of competence or ability of a leader is still weak. Leadership conflicts also occur due to differences in opinions, stances, beliefs, cultural differences, differences in interests, conflicts also occur between superiors and subordinates, even conflicts with students and parents including the community or external parties. Thus it can be concluded that leadership conflicts in the management of educational institutions occur due to weak management levels, competencies and abilities. So it can be suggested that if you want to minimize conflict among the leadership, then improve the management of better educational institutions in Indonesia.Keywords: Conflict, Leadership, Management of Educational Institutions, Madrasah Aliyah Abstrak: Dalam pengelolaan lembaga pendidikan masih menciptakan konflik, dikarenakan sebagian kepemimpinan masih lemah pada tingkat manajemen, kompetensi dan kemampuan kepemimpinan dalam mengelola lembaga pendidikan. Tujuan tulisan ini selain memetakan juga menganalisis konflik kepemimpinan dalam pengelolaan lembaga pendidikan Madrasah Aliyah di Indonesia. Menggunakan metode kualitatif deskriptif. Sumber data dari buku-buku ilmiah, artikel ilmiah, jurnal ilmiah baik cetak maupun online, baik nasional maupun internasional. Hasil penelitian menunjukkan bahwa konflik kepemimpinan dalam pengelolaan pendidikan terjadi karena tingkat pengelolaan lembaga pendidikan oleh sebagian kepemimpinan kepala Madrasah Aliyah masih lemah seperti lemah dalam perencanaan, pengorginisasian, pergerakan, pengarahan dan pengawasan atau kontrol. Konflik kepemimpinan juga terjadi karena tingkat kompetensi atau kemampuan seseorang pemimpinan yang masih lemah. Konflik kepemimpinan juga terjadi karena perbedaan pendapat, pendirian, keyakinan, perbedaan kebudayaan, perbedaan kepentingan, konflik juga terjadi antara atasan dengan bawahannya, bahkan konflik dengan siswa dan orang tua termasuk masyarakat atau pihak eksternal. Dengan demikian dapat disimpulkan bahwa konflik kepemimpinan dalam pengelolaan lembaga pendidikan terjadi karena tingkat pengelolaan, kompetensi dan kemampuan kepemimpinan masih lemah. Sehingga dapat disarankan jika ingin meminimalisir konflik dikalangan kepemimpinan, maka tingkatkan pengelolaan lembaga pendidikan yang lebih baik di Madrasaha Aliyah Indonesia. Kata kunci: Konflik, Kepemimpinan, Pengelolaan Lembaga Pendidikan, Madrasah Aliyah